Comprehensive assessment and material analysis of a heritage structure: proposing an effective restoration and retrofitting strategy - Prithvi Prabhu; Neethu Urs B A; Tahera; Meghashree M; Adithya Tantri (Journal of Asian Architecture and Building Engineering)
Heritage structures are essential for preserving national history and cultural identity, embodying significant events and unique aesthetic value. However, they face increasing threats from negligence, environmental degradation, and urbanization. The Cubbon Rooms in Bangalore, Karnataka, have suffered considerable deterioration due to a lack of preservation efforts. This study seeks to develop an effective restoration strategy for The Cubbon Rooms through a comprehensive assessment of its condition and material composition. It involved extensive documentation and advanced damage analysis, utilizing techniques such as Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray spectroscopy (EDS), and Ultrasonic Pulse Velocity (UPV) testing. These methods revealed various types of distress, including surface erosion, cracking, and material degradation caused by environmental factors and aging. SEM and EDS analyses provided crucial insights into the microstructural integrity of the materials, while UPV testing assessed internal soundness. A tailored restoration model was created, prioritizing the preservation of the building’s historical form and enhancing structural integrity. This model includes material-specific repair methods, environmental protection measures, and maintenance protocols. Implementing this strategy will extend the life of The Cubbon Rooms, safeguard its architectural significance, and promote resilience against future deterioration, serving as a blueprint for similar heritage preservation efforts.